PENGARUH PELAYANAN, PEMERIKSAAN DAN SANKSI PAJAK TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI PADA KANTOR PELAYANAN PAJAK PRATAMA DEPOK CIMANGGIS) - Parso Parso (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2020)
AbstractThis research aims to analyze the effect of tax quality, tax audits, and tax penalties on the compliance of personal taxpayers. Attribution Theory explains that the effect of tax service, tax audits and tax penalties are external factors that affect taxpaver compliance. Where the services provided by tax officials affect taxpayer compliance, while the tax audit and penalities make taxpayers have indirect compliance with the accuracy and complicnce of taxpayers personally in implementing taxr activities. Based on the theory of social learning this theory should make observations and experience directly to participate in terms of tax complicance. Respondents in this research are individual taxpayers registered in KPP Pratama Depok Cimcnggis. The analysis used in this research is using SPSS 21.0 for Windows software. The analysis technique used multiple regression amalysis with the least squares equation and Iypothesis test using t-statistic and F test to test the partial and simultaneous regression coefficient, validity test, reliability test, amd elassical assumption test which include normality test, multicolonierity test, and heteroscedasticity test. This stucy shows that the understanding of tax qualities, tax audits and the tax penalties, and the sanetions applicable taxes and significant positive effect on tax compliance.